A Select Study of Consumer Purchase Behavior of Organic Food in Delhi NCR Region - Chakrabarti, Somnath (Indian Journal of Marketing, 2010)
Consumers worldwide are becoming increasingly concerned about nutrition, health and the quality of their food (Gil et al., 2000). One of the key ways that environment and health consciousness is getting reflected is through consumers' increased interest in organic food (von Alvensleben, 1998). More than 140 countries are now producing certified organic food with 32.2 million hectares of agricultural land being managed organically globally by more than 1.2 million producers (Willer and Kilcher, 2009). Global sales of organic products had reached 46.1 billion US dollars in 2007 (Willer and Kilcher, 2009). Schlegelmich et al. (1996) have indicated that the increase in environmental consciousness has had a profound impact on consumer behavior whereby, the green product is expanding at a fast pace.